2013
DOI: 10.1371/journal.pone.0063750
|View full text |Cite
|
Sign up to set email alerts
|

Stress Relaxation Analysis Facilitates a Quantitative Approach towards Antimicrobial Penetration into Biofilms

Abstract: Biofilm-related infections can develop everywhere in the human body and are rarely cleared by the host immune system. Moreover, biofilms are often tolerant to antimicrobials, due to a combination of inherent properties of bacteria in their adhering, biofilm mode of growth and poor physical penetration of antimicrobials through biofilms. Current understanding of biofilm recalcitrance toward antimicrobial penetration is based on qualitative descriptions of biofilms. Here we hypothesize that stress relaxation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
80
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(86 citation statements)
references
References 30 publications
4
80
0
2
Order By: Relevance
“…The extent to which specific different hydrodynamic factors contribute is still dependent on the specifics of the instruments. On the other hand, He and co-workers found that powered brushing in non-contact mode changed the viscoelastic properties of the oral biofilm resulting in increased penetration of antimicrobial compounds into the biofilm [24,25]. Therefore, even if biofilms are not totally removed by sonic brushing, they may be more susceptible to antimicrobials thereafter.…”
Section: Discussionmentioning
confidence: 99%
“…The extent to which specific different hydrodynamic factors contribute is still dependent on the specifics of the instruments. On the other hand, He and co-workers found that powered brushing in non-contact mode changed the viscoelastic properties of the oral biofilm resulting in increased penetration of antimicrobial compounds into the biofilm [24,25]. Therefore, even if biofilms are not totally removed by sonic brushing, they may be more susceptible to antimicrobials thereafter.…”
Section: Discussionmentioning
confidence: 99%
“…), with the motion of one controlled to impose a predefined strain or stress schedule. Biofilms can be grown ex situ and transplanted to the rheometer, either intact on plates [41,66] or by a destructive process [55,104], or the rheometer modified to permit growth in situ [69,70]. Macrorheometry can extract bulk properties [68,82] but is not well suited to studying heterogeneities.…”
Section: Experimental Biofilm Rheologymentioning
confidence: 99%
“…The free surfaces of biofilms in their native state can be compressed globally [41,71], or locally such as performed by atomic force microscopy [14,54], and force-displacement relations and relaxation curves measured. Heterogeneity can be probed by multi-site sampling [48].…”
Section: Macro and Micro-indentationmentioning
confidence: 99%
See 1 more Smart Citation
“…Yaptığı incelemelerde çok sayıda küçük canlının insan diş yüzeyinde yaşadığını fark eden Leeuwenhoek, dişlerini sirke ile yıkadıktan sonra da örnek alarak inceleme yapmış ve dişindeki tortu dışında yaşayan hayvancıkların öldüğünü ancak tortu içerisinde bulunanlara sirkenin etki etmediğini görmüştür [1].…”
Section: Introductionunclassified